Cervical vagal nerve schwannoma induced arrhythmia: a rare case report and literature review - Pin Ye; Changhuai He; Yunfei Chen; Hongxiao Wu; Yiqing Li; Chuanqi Cai; Ping Lü (BMC Neurology, 2022)
Abstract Background Schwannomas are benign tumors deriving from the sheath of cranial and peripheral nerves. The vagus nerve is comprised of a complex neuro-endocrine-immune network that maintains homeostasis, most tracts of it play a role in parasympathetic activity. We present an example of a rare cervical vagal schwannoma case accompanied by arrhythmia. Case presentation A 35-year-old female patient with a left cervical vagus schwannoma and ventricular arrhythmia underwent schwannoma resection in the operating room. The patient’s suppressed heart rate increased after tumor removal, and the cardiac rhythm returned to normal postoperatively. Pathological examination demonstrated the diagnosis of schwannoma. Conclusions This case explains the link between the vagus nerve and the cardiovascular system, proving that a damaged cervical vagus nerve can inhibit the heart rate and lead to arrhythmias, and eventually requiring surgical intervention.